2000
DOI: 10.1063/1.1323856
|View full text |Cite
|
Sign up to set email alerts
|

High-mobility AlGaN/GaN heterostructures grown by molecular-beam epitaxy on GaN templates prepared by hydride vapor phase epitaxy

Abstract: We report on the growth and transport properties of high-mobility two-dimensional electron gases (2DEGs) confined at the AlGaN/GaN interface grown by plasma-assisted molecular-beam epitaxy on GaN templates prepared by hydride vapor phase epitaxy. We have grown samples over a broad range of electron densities ranging from ns=6.9×1011 to 1.1×1013 cm−2, and at T=4.2 K, observe a peak mobility of 53 300 cm2/V s at a density of 2.8×1012 cm−2. Magnetotransport studies on these samples display exceptionally clean sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(41 citation statements)
references
References 10 publications
3
35
1
2
Order By: Relevance
“…It was already shown that due to the piezoelectric doping mechanism, the concentration of electrons in 2DEG is controlled by the thickness and Al content of AlGaN layer grown on Ga polarity side [1][2][3]. The very high electron concentration of 2DEG -10 13 cm -2 obtained without additional modulation doping together with the mobility of 1000-2000 cm 2 /Vs makes GaN/AlGaN heterostuctures very attractive for high power, high speed transistors [4]. On the other hand GaN/AlGaN heterojunctions are interesting for fundamental physics studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that due to the piezoelectric doping mechanism, the concentration of electrons in 2DEG is controlled by the thickness and Al content of AlGaN layer grown on Ga polarity side [1][2][3]. The very high electron concentration of 2DEG -10 13 cm -2 obtained without additional modulation doping together with the mobility of 1000-2000 cm 2 /Vs makes GaN/AlGaN heterostuctures very attractive for high power, high speed transistors [4]. On the other hand GaN/AlGaN heterojunctions are interesting for fundamental physics studies.…”
Section: Introductionmentioning
confidence: 99%
“…HVPE films can be used as templates for molecular beam epitaxial growth of GaN devices. 1 Since this highly conducting interfacial layer co-exists with the rest of the GaN film and affects carrier transport at all temperatures, 2 a better understanding of its nature and origin is desired. Previous Hall measurements show that, below a certain temperature, the measured carrier density (n) increases and the mobility (µ) decreases as the temperature decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the electron mobility (µ) of the 2DEG can exceed 50,000 cm 2 /Vs at low temperatures. 1,2 Based on what is known about the 2DEG system in AlGaAs/GaAs heterostructures, growth morphology and interface roughness could have a dramatic impact on the transport properties of the 2DEG. 3 In the AlGaN/GaN system, due to the lack of suitable substrates, dislocations and their associated electronic states present additional factors that can affect surface morphology and 2DEG transport.…”
mentioning
confidence: 99%